Educação e Comunicação como prática de pesquisa - Porto, Tânia Mara Esperon (Comunicação & Educação, 1998)
The article reports on the development of the teaching practice in the Master's level course in Education at the College of Education at the Universidade Federal de Pelotas - RS. A group of educators carried out experiments in the teaching-researching modality aiming at focusing on education as a communication process. The methodology that was adopted privileged the subjects' critical autonomy in contact with their day to day experience, allowing for the socialization of learned knowledge, relating theory and practice. It gives examples of work done by graduate students as well as their points of view on the methodology that was developed.